Potency of Non-Fungicide Chemicals for Maize Inducing Resistance against Downy Mildew - Muhammad Habibullah; Christanti Sumardiyono; Ani Widiastuti (Universitas Gadjah Mada, 2020)
Downy mildew disease control is a big challenge in Indonesia due to ability of pathogen adaptation and favorable environmental condition to the disease. Self-resistance induction by activating plant defense mechanism is a valuable control method to be developed in the future due to its environmentally safety. This study aimed to determine potency of non-fungicide chemicals to suppress downy mildew of maize. The tested chemicals were benzoic acid, sodium benzoic acid, salicylic acid, thiamine, saccharin, and aspirin with a concentration of 2000 ppm. Disease incidence, disease severity, disease progress, leaf tissue lignification, plant growth, chlorophyll content, and plant dry weight were observed to find out the effect of the chemicals application in maize against downy mildew. Results showed that seed application of benzoic acid was able to reduce disease incidence and disease severity by 80%. Benzoic acid treated plants were categorized as moderately resistant until 5-week observation, while inoculated plants (positive control) were susceptible. Based on AUDPC values, plants induced by the chemicals had slower disease development rates compared to positive control. Lignification around the stomata occured in all inoculated plants treated by chemicals. Plant growth between chemical treated plants and negative control (non-inoculated plant) mainly showed no significant different, elaborated that those chemicals were applicable. Chlorophyll content in chemical treated plants was also similar to those of negative control plant. Based on these results, benzoic acid was promoted to be further investigated as maize resistance inducer against downy mildew.